TO THE QUESTION OF HISTORY OF FORMATION AND DEVELOPMENT OF INDEPENDENT KAZAKHSTAN - Ayupova, Z. K.; Kussainov, D. U.; Kozlowski3, Waldemar (Scientific Journal of Pedagogy and Economics, 2018)
The concept “constitution” is applied in two meanings. In formal sense the legal Constitution is the fundamental law of the state, regulated the socio-economic system, the form of government and form of administration; also the legal status of the personality. It is the document, which defines the constitutional and legal status of the official organs. However, during the legal reforms in our society the practical application and whole situation have changed: there are new institutions were created; new constitutional laws, etc. were adopted. In the practice there is such procedure of the government, which can significantly differ from the official order, fixed in the Constitution. This real procedure of the election and appointment of the government has called the actual Constitution or the Constitution in material sense of the word. The actual and legal Constitutions can both coincide and disperse. In some countries the political elite seeks to govern, besides the Constitution. It turns out that, from one hand, the constitution is necessary in any democratic state. From the other hand, the Constitution conflicts with the reality. The historical collision between legality and expediency every time is solved, depending on the arrangement of the political forces in the society.